Gelombang Ideologi Islam Transnasional dalam Sekolah Islam Terpadu - Herianda Dwi Putra Siregar (Jurnal Ilmu Sosial Indonesia (JISI), 2021)
Abstract. The development of Integrated Islamic schools is in line with the increasing symptoms of religious conservatism whose roots can be found from tarbiyah movements on public campuses, such as UGM, UI, ITB. In general, Integrated Islamic individuals or groups present themselves with an Islamic identity by returning to "authentic Islam", as practiced by the salaf ash-shalih. Unfortunately, the concept of authenticity differs from one group to another. This article concludes that the Integrated Islamic School is not only aimed at transmitting Islamic teachings, but also as an effort to encourage people to be more Islamic.Keywords: Transnational Islam, Integrated Islamic Schools, PKS and Urban Communities.Abstrak. Perkembangan sekolah Islam Terpadu seiring dengan meningkatnya gejala konservatisme keagamaan yang akar-akarnya dapat ditemukan dari gerakan-gerakan tarbiyah di kampus-kampus umum, seperti UGM, UI, ITB. Secara umum, Individu atau kelompok Islam Terpadu menampilkan diri dengan identitas ke-Islaman dengan kembali pada “Islam autentik”, sebagaimana yang dipraktikkan oleh salaf ash-shalih. Sayangnya konsepsi tentang ke-autentikan mempunyai perbedaan antara satu kelompok dengan kelompok yang lain. Artikel ini menyimpulan bahwa Sekolah Islam Terpadu bukan hanya bertujuan untuk mentransmisikan ajaran-ajaran Islam semata, namun juga sebagai upaya untuk mendorong masyarakat untuk lebih Islami.Kata Kunci: Islam Transnasional, Sekolah Islam Terpadu, PKS dan Masyarakat Urban.